Are risk management disclosures relevant to firm's profitability? A Tanzanian case - Mwenda, Beny; ibrahim, magwana (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2023)
This research investigated the relevance of risk management disclosures on firm’s profitability in Tanzania. Risk Management Disclosures (RMD) were measured using a disclosure index adopted from the Tanzania’s Capital Market Securities Act (CMSA) regulations while firms' profitability was represented by Return on Equity (ROE) and Return on Assets (ROA). A quantitative research approach was used, secondary data was collected from the annual reports of firms listed on the Dar es Salaam Stock Exchange (DSE) for the period ranging from 2010 to 2021. Panel regression modeling was used to estimate the parameters in this study. Results demonstrated that Risk Management Disclosure (RMD) was relevant to firm’s profitability since it had a significant and positive effect on ROA and ROE. Based on this, the research draws the conclusion that risk management disclosures are important as they assisted Tanzanian businesses to become more profitable. We recommend firms to include more risk management-related information in their annual reports for the benefit of users of financial statements. The study contributes to the existing body of knowledge by by adding new variables to the existing models